Lignin-solubilizing ability of actinomycetes isolated from termite (Termitidae) gut. - Pasti, M B (1990)
The lignocellulose-degrading abilities of 11 novel actinomycete strains isolated from termite gut were determined and compared with that of the well-characterized actinomycete, Streptomyces viridosporus T7A. Lignocellulose bioconversion was followed by (i) monitoring the degradation of [14C]lignin- and [14C]cellulose-labeled phloem of Abies concolor to 14CO2 and 14C-labeled water-soluble products, (ii) determining lignocellulose, lignin, and carbohydrate losses resulting from growth on a lignocellulose substrate prepared from corn stalks (Zea mays), and (iii) quantifying production of a water-soluble lignin degradation intermediate (acid-precipitable polymeric lignin). The actinomycetes were all Streptomyces strains and could be placed into three groups, including a group of five strains that appear superior to S. viridosporus T7A in lignocellulose-degrading ability, three strains of approximately equal ability, and three strains of lesser ability. Strain A2 was clearly the superior and most effective lignocellulose decomposer of those tested. Of the assays used, total lignocellulose weight loss was most useful in determining overall bioconversion ability but not in identifying the best lignin-solubilizing strains. A screening procedure based on 14CO2 evolution from [14C-lignin]lignocellulose combined with measurement of acid-precipitable polymeric lignin yield was the most effective in identifying lignin-solubilizing strains. For the termite gut strains, the pH of the medium showed no increase after 3 weeks of growth on lignocellulose. This is markedly different from the pattern observed with S. viridosporus T7A, which raises the medium pH considerably. Production of extracellular peroxidases by the 11 strains and S. viridosporus T7A was followed for 5 days in liquid cultures.(ABSTRACT TRUNCATED AT 250 WORDS)